Hexose/pentose ratio in rhizosphere exudates-mediated soil eutrophic/oligotrophic bacteria regulates the growth pattern of host plant in young apple–aromatic plant intercropping systems - Zhao, Mengnan; Sun, Yue; Dong, Meilin; Zhang, Kui; Zhang, Jie; Qin, Xiaoxiao; Yao, Yuncong (Frontiers in Microbiology, 2024)
Introduction The positive effect of intercropping on host plant growth through plant–soil feedback has been established. However, the mechanisms through which intercropping induces interspecific competition remain unclear. Methods In this study, we selected young apple trees for intercropping with two companion plants: medium growth-potential Mentha haplocalyx Briq. (TM) and high growth-potential Ageratum conyzoides L. (TA) and conducted mixed intercropping treatment with both types (TMA) and a control treatment of monocropping apples (CT). Results Our findings revealed that TM increased the under-ground biomass of apple trees and TA and TMA decreased the above-ground biomass of apple trees, with the lowest above-ground biomass of apple trees in TA. The above- and under-ground biomass of intercrops in TA and TMA were higher than those in TM, with the highest in TA, suggesting that the interspecific competition was the most pronounced in TA. TA had a detrimental effect on the photosynthesis ability and antioxidant capacity of apple leaves, resulting in a decrease in above-ground apple biomass. Furthermore, TA led to a reduction in organic acids, alcohols, carbohydrates, and hydrocarbons in the apple rhizosphere soil (FRS) compared to those in both soil bulk (BS) and aromatic plant rhizosphere soil (ARS). Notably, TA caused an increase in pentose content and a decrease in the hexose/pentose (C6/C5) ratio in FRS, while ARS exhibited higher hexose content and a higher C6/C5 ratio. The changes in exudates induced by TA favored an increase in taxon members of Actinobacteria while reducing Proteobacteria in FRS compared to that in ARS. This led to a higher eutrophic/oligotrophic bacteria ratio relative to TM. Discussion This novel perspective sheds light on how interspecific competition, mediated by root exudates and microbial community feedback, influences plant growth and development.